Public Management Reform and Modernization - Călin HINȚEA (Transylvanian Review of Administrative Sciences, 2010)
Public Management Reform and Modernization, Trajectories of Administrative Change in Italy, France, Greece, Portugal and Spain, Published by Edward Elgar Publishing Limited, Glos, UK, 2009